2023
DOI: 10.18844/ijlt.v10i1.3140
|View full text |Cite
|
Sign up to set email alerts
|

Teaching digital electronics course for electrical engineering students in cognitive domain

Abstract: Di gi tal electroni cs course is one of the very fundamental courses for the s tudents of undergradua te programme of electrical and electroni c engineering (EEE) and the othe r undergradua te engineering dis ciplines. Therefore, 'di gital electronics ' shall be taught effecti vel y, so tha t s tudents ca n appl y the knowledge lea rned to sol ve thei r real -life engineering problems . A tea cher needs to adopt new tea chi ng methodologies to a ttra ct current genera tion of s tudents , and thus , to prepa re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…Bloom's taxonomy will be followed for teaching, learning and assessment of the students. These were found very effective in various universities in Bangladesh (Bhuyan, 2014;Bhuyan, Khan & Rahman, 2014;. Besides, students are being motivated in the classes to study their respective courses .…”
Section: Recommendations Based On Findings and Discussionmentioning
confidence: 99%
“…Bloom's taxonomy will be followed for teaching, learning and assessment of the students. These were found very effective in various universities in Bangladesh (Bhuyan, 2014;Bhuyan, Khan & Rahman, 2014;. Besides, students are being motivated in the classes to study their respective courses .…”
Section: Recommendations Based On Findings and Discussionmentioning
confidence: 99%
“…Since all students' views will not be the same, marks will vary based on topic, writing quality, the number of words/pages, grammar and spelling errors etc. h. There should be some critical thinking and higher order skills-related cognitive domain questions (Bhuyan, 2014;Bhuyan & Khan, 2014) to distinguish between high and lowperforming students. In viva voce, such type of questions should be asked to assess and evaluate the course outcome (CO) attained (Bhuyan & Khan, 2020;Bhuyan & Tamir, 2020) by each student individually, and for this purpose, the assessment plan and questions should be set accordingly.…”
Section: Preparation For Online Classmentioning
confidence: 99%
“…To provide students with the necessary knowledge of the capstone project, various levels of the cognitive domain in the teaching-learning strategies are followed in this course. It has been observed that this technique is more realistic than that in the traditional technique of teachinglearning strategies (Bhuyan, 2014;. The measurement of the attainment level of each CO and PO is carried out by using one or more components of the rubricbased assessment tools (Table 1).…”
Section: Co-po Mapping and Performance Assessmentmentioning
confidence: 99%